2005
DOI: 10.1007/s10600-006-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids of Plants from the Genus Tamarix

Abstract: The flavonoid composition of plants is one of the adaptive variables in their adjustment to environmental conditions [1]. Therefore, an investigation of the polyphenol composition of plants from the genus Tamarix (Tamaricaceae), which are halophytes (salt tolerant plants), is considered timely [2].This communication continues an earlier study of Tamarix elongata Ledeb. and T. laxa Will. (aerial part) that were collected in the Aral and Almaty regions during flowering [3,4]. Quantitative analysis showed 1.45 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…The chemical investigation of various Tamarix species was reported. Gallic acid, flavones, and flavonols were among the polyphenols found in this study that were recognized as compounds that had previously been found in other species of Tamarix [ 34 , 95 ]. For example, a study on the alcohol-soluble fraction of an aqueous extract of T. nilotica aerial parts collected from Egypt and Saudi Arabia was discussed by Sekkien A. et al 2018 [ 30 ].…”
Section: Discussionsupporting
confidence: 56%
“…The chemical investigation of various Tamarix species was reported. Gallic acid, flavones, and flavonols were among the polyphenols found in this study that were recognized as compounds that had previously been found in other species of Tamarix [ 34 , 95 ]. For example, a study on the alcohol-soluble fraction of an aqueous extract of T. nilotica aerial parts collected from Egypt and Saudi Arabia was discussed by Sekkien A. et al 2018 [ 30 ].…”
Section: Discussionsupporting
confidence: 56%
“…Regarding the other main polyphenolics, isorhamnetin was reported to have been identified from T. hispida , T. elongata and T. laxa which were all collected from southern Kazakhstan [11,14]. Quercetin was a common compound in the Tamarix species and had been identified by several researchers [5,8,10,11,15]. Compared to the results of this work, other researchers obtained different polyphenolic compounds from Tamarix .…”
Section: Resultsmentioning
confidence: 50%
“…Flavonoids, which are one group of polyphenolics, are secondary metabolites in plants and act as antioxidants [6]. Many types of polyphenols, such as flavonoids and phenolic acids, were reported in Tamarix species [1,2,7,8,9,10,11]. In this work, the TPC of T. ramosissima bark extract was 323.45 mg gallic acid equivalent (GAE)/g, and the TFC was 87.32 quercetin equivalent (QE)/g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their structures were elucidated by chromatography; alkaline degradation; acetylation; methylation; UV, IR, and PMR spectroscopy; and melting point [3][4][5][6][7].…”
mentioning
confidence: 99%